A self-healing semi-solid lithium battery separator and its preparation method
By introducing microcapsule technology into semi-solid lithium battery separators, the polymerization and repair of the internally filled monomer materials after damage is used to solve the problem of insufficient self-repair capability of the existing separator, and the rapid and effective self-repair of the separator and significant improvement of the battery performance are achieved.
Patent Information
- Application Number
- CN202411929513.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-04
AI Technical Summary
The existing semi-solid lithium battery separators lack effective self-repair mechanisms after mechanical damage, resulting in degradation of battery performance or failure, increasing maintenance costs and difficulty.
A diaphragm made of composite material composed of microcapsules is filled with monomer materials that can flow out and polymerize solid polymers when damaged. The polymerization reaction is promoted by photoinitiators or thermal initiators to achieve self-healing of the diaphragm.
After diaphragm damage, the self-healing process can be started in 5 minutes and completed in 30 minutes, restoring at least 90% of the original mechanical strength and electrochemical performance, extending the battery life and improving safety.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of semi-solid lithium batteries, in particular to a semi-solid lithium battery separator with a self-repairing function, and a corresponding preparation method. Background Art
[0002] Semi-solid lithium batteries have attracted widespread attention due to their high energy density and safety. However, the separator materials used in semi-solid lithium batteries still face challenges in terms of mechanical strength, chemical stability and lifespan. In particular, under long-term use or extreme conditions, the separator may be damaged, resulting in battery performance degradation or even failure.
[0003] Existing diaphragm technology lacks an effective self-repair mechanism. Once damaged, the diaphragm or the entire battery often needs to be replaced, increasing costs and maintenance difficulties.
[0004] The present invention aims to solve the problem of insufficient repair ability of existing diaphragm technology after damage and improve the overall performance of semi-solid lithium batteries. Summary of the invention
[0005] The purpose of the present invention is to develop a semi-solid lithium battery separator with self-repairing function, and a corresponding method for preparing the semi-solid lithium battery separator with self-repairing function, so as to improve the safety, stability and service life of the battery.
[0006] The present invention aims to achieve self-repair of the diaphragm after damage by introducing microcapsule technology, thereby maintaining or restoring the original performance of the battery diaphragm.
[0007] The technical solution of the present invention includes: a diaphragm, which is made of a composite material composed of microcapsules with self-repairing ability. These microcapsules contain monomers that can flow out when the diaphragm is damaged and form solid polymers at the damaged part, thereby realizing the self-repairing function. The shell material of the microcapsule is selected from materials with high chemical stability and good mechanical strength to ensure that it will not break under normal working conditions of the battery.
[0008] The innovation of the present invention lies in the design of microcapsules and the preparation method of the diaphragm. By optimizing the size, wall thickness and monomer filling amount of the microcapsules, as well as the distribution and concentration of the microcapsules in the diaphragm, rapid and effective self-repair is achieved while maintaining good electrochemical and mechanical properties of the diaphragm.
[0009] The present invention provides a semi-solid lithium battery diaphragm with self-repairing function, characterized in that the diaphragm comprises a plurality of microcapsules, wherein the microcapsules are filled with monomer materials that can flow out when the diaphragm is damaged and form solid polymers at the damaged portion.
[0010] Further preferably, the shell material of the microcapsule is selected from polyurethane, polylactic acid or other polymer materials with good chemical stability and mechanical strength.
[0011] Further preferably, the monomer material is an acrylate monomer, and the microcapsule also contains a small amount of photoinitiator or thermal initiator to promote rapid polymerization of the monomer.
[0012] Further preferably, the photoinitiator includes benzophenone, dibenzophenone, diphenylethylene, etc. The typical amount of the photoinitiator used ranges from 0.1% to 5% of the total amount of the monomer material to ensure sufficient polymerization rate and polymer performance.
[0013] Further preferably, the thermal initiator includes azobisisobutyronitrile (AIBN), persulfate, ammonium persulfate, etc. The typical amount of thermal initiator ranges from 0.1% to 3% of the total amount of monomer material to ensure that the polymerization reaction can be effectively initiated under the required temperature conditions while maintaining good polymer properties.
[0014] Further preferably, the base material of the diaphragm is selected from polyethylene, polypropylene, polyvinyl alcohol or a composite material thereof.
[0015] More preferably, the diameter of the microcapsules ranges from 1 micron to 50 microns.
[0016] Further preferably, the distribution of the microcapsules in the diaphragm is uniform. Specifically, the volume fraction of the microcapsules is limited to 5% ± 1%, ensuring that the microcapsules can be fully distributed in the diaphragm material. The scanning electron microscope (SEM) image of the diaphragm slice is analyzed by image analysis software, and the distribution uniformity index calculated is 0.95, which can indicate that the distribution of the microcapsules in the diaphragm is close to an ideal uniform state. The average spacing between the microcapsules is determined by image analysis to be 10 microns, the standard deviation is 2 microns, and the coefficient of variation (CV) is 20%.
[0017] Further preferably, the separator comprises a reinforcing material capable of improving the mechanical strength and electrochemical stability of the separator.
[0018] Further preferably, the reinforcing material is selected from nanoparticles, carbon nanotubes, graphene or a combination thereof.
[0019] Further preferably, the membrane has the ability to start self-repairing within 5 minutes after damage, and the self-repairing process is completed within 30 minutes.
[0020] Further preferably, the separator can recover at least 90% of its original mechanical strength and electrochemical performance after self-repair.
[0021] The present invention also provides a method for preparing a semi-solid lithium battery separator with self-repairing function, comprising the following steps: preparing microcapsules containing monomer materials; uniformly dispersing the microcapsules in a separator base material; forming a separator; and post-treating the formed separator to improve its mechanical strength and electrochemical stability.
[0022] Further preferably, the preparation of the microcapsules includes emulsion polymerization, phase transfer method or microfluidics technology.
[0023] Further preferably, the monomer material is an acrylate monomer, and a photoinitiator or a thermal initiator is added during the preparation of the microcapsules.
[0024] Further preferably, the membrane base material is selected based on its electrochemical stability and mechanical strength, and is selected from polyethylene, polypropylene, polyvinyl alcohol or a composite thereof.
[0025] Further preferably, the dispersion of the microcapsules in the membrane-based material is achieved by mechanical stirring, ultrasonic dispersion or high shear mixing.
[0026] Further preferably, the step of forming the diaphragm includes coating, extrusion, dipping or other suitable molding techniques.
[0027] Further preferably, the post-treatment step includes heat treatment, UV curing or chemical cross-linking to improve the mechanical strength and electrochemical stability of the separator.
[0028] Further preferably, the diameter of the microcapsules is controlled within a range of 1 micron to 50 microns by adjusting reaction conditions during preparation.
[0029] Further preferably, the method further comprises adding reinforcing materials, such as nanoparticles, carbon nanotubes, graphene or a combination thereof, into the separator to further improve the mechanical strength and electrochemical stability of the separator.
[0030] It is necessary to further explain that the main material of the diaphragm is a polymer material with good electrochemical stability and mechanical strength, such as polyethylene (PE), polypropylene (PP) or their composite materials. The shell material of the microcapsule is polyurethane (PU), polylactic acid (PLA) or other polymer materials with good chemical stability and mechanical strength to ensure stability under battery working conditions. The monomer material filled in the microcapsule is a monomer that can quickly polymerize under specific conditions to form a solid polymer, such as acrylate monomers. These monomers can react quickly when the diaphragm is damaged and fill the damaged area.
[0031] The working principle of the self-repair mechanism is based on the fact that the microcapsules rupture when the diaphragm is mechanically damaged, releasing the filled monomer material. The released monomer material undergoes polymerization reaction at the damaged part to form a solid polymer, thereby repairing the diaphragm damage. In order to promote the rapid polymerization of the monomer, a small amount of photoinitiator or thermal initiator can also be added to the microcapsule to accelerate the polymerization reaction by light or heating.
[0032] The preparation process of semi-solid lithium battery separator with self-healing function includes the following key steps: first, prepare microcapsules containing monomers, initiators and other necessary additives; second, evenly disperse the microcapsules in the separator base material solution; then, form the separator by coating, extrusion or other suitable methods, and dry and cure it; finally, heat treat or chemically cross-link the separator to improve its mechanical strength and chemical stability. DETAILED DESCRIPTION
[0033] Example 1: Preparation of a self-healing diaphragm based on polyethylene (PE) substrate and polyurethane (PU) shell microcapsules. First, PU microcapsules with a diameter of 5 microns were prepared by emulsion polymerization, and the filler was methyl methacrylate (MMA) and a small amount of photoinitiator. Then, these microcapsules were evenly dispersed in a PE solution at a weight ratio of 5%. The diaphragm was formed by a coating method, then dried at 70°C for 12 hours, and finally cross-linked and cured by ultraviolet light irradiation to obtain a semi-solid lithium battery diaphragm with self-healing function.
[0034] Example 2: A mixture of polypropylene (PP) and polylactic acid (PLA) was used as the membrane substrate, the shell material of the microcapsule was PLA, and the filler was epoxy resin and thermal initiator. The diameter of the microcapsule was adjusted to 10 microns and dispersed in the PP / PLA mixed solution at a weight ratio of 10%. The membrane was prepared by extrusion and heat-treated at 80°C for 4 hours after drying to activate the self-healing function.
[0035] Example 3: Using polyvinyl alcohol (PVA) as the substrate, microcapsules containing divinylbenzene (DVB) monomer and photoinitiator were prepared, and the shell material of the microcapsules was selected as polyurethane (PU). The microcapsules were dispersed in the PVA solution at a weight ratio of 8%, and the diaphragm was prepared by the dipping method. After drying, it was irradiated with ultraviolet light at room temperature for 2 hours to complete the crosslinking and curing process to obtain a self-repairing diaphragm. This diaphragm not only has good mechanical properties and electrochemical stability, but also can quickly achieve self-repair after damage through ultraviolet light irradiation, restoring its integrity and function.
[0036] In order to evaluate the performance of the self-healing semi-solid lithium battery separator, the product was evaluated using mechanical properties test, electrochemical properties test and self-healing efficiency test.
[0037] 1. Mechanical properties test:
[0038] (1) Sample preparation: A sample with a size of 10 mm wide and 50 mm long was cut out from the semi-solid lithium battery separator with self-healing function.
[0039] (2) Damage creation: A microcrack with a length of approximately 2 mm was created in the center of the diaphragm sample using a sharp tool to simulate the damage that may occur in actual use.
[0040] (3) Self-repairing conditions: The damaged membrane samples were placed in an environment of 25°C and 50% relative humidity, and the self-repairing process was allowed to proceed for 24 hours.
[0041] (4) Tensile test:
[0042] - Equipment: Tensile test was performed using an electronic universal testing machine.
[0043] - Conditions: The test was carried out at room temperature and the stretching rate was set at 5 mm / min.
[0044] - Parameter recording: record the maximum tensile strength (MPa) and elongation at break (%) of the separator.
[0045] (5) Test results:
[0046] -Before self-repair:
[0047] -Maximum tensile strength: 2.5MPa
[0048] - Elongation at break: 120%
[0049] -Since repair:
[0050] -Maximum tensile strength: 2.3MPa (recovered to 92% of the original value)
[0051] - Elongation at break: 108% (recovered to 90% of original value)
[0052] According to the above test results, it can be observed that the maximum tensile strength and elongation at break of the self-repaired diaphragm samples have decreased, but still recovered to 92% and 90% of the original values, respectively. This shows that the diaphragm has good self-repairing ability and can significantly restore its mechanical properties through the self-repair process after damage. Although the performance after self-repair is slightly reduced, this is acceptable in practical applications, especially considering that the self-repair function can extend the service life of the diaphragm and improve the safety of the battery.
[0053] 2. Electrochemical performance test:
[0054] (1) Ionic conductivity test:
[0055] -The ionic conductivity of the separators was measured using electrochemical impedance spectroscopy (EIS) at room temperature.
[0056] - Test frequency range: 1MHz to 0.1Hz.
[0057] -Extract the interfacial resistance of the electrolyte from the Nyquist plot and calculate the ionic conductivity.
[0058] (2) Electrochemical window test:
[0059] -The electrochemical stability window of the separator in lithium batteries was tested by cyclic voltammetry (CV).
[0060] - Scan rate: 5mV / s.
[0061] - Potential range: -0.5V to 5.0V (vs. Li / Li+).
[0062] (3) Battery cycle performance test:
[0063] -The separator was applied to lithium batteries and the charge and discharge cycle test was performed.
[0064] -Charge and discharge rate: 0.5C.
[0065] - Number of cycles: at least 500 times.
[0066] -Record the charge and discharge capacity and Coulombic efficiency of each cycle.
[0067] (4) Test results:
[0068] -The ionic conductivity obtained by the test is 1.0×10 -3 S / cm, indicating that the membrane has good ion conductivity.
[0069] -Cyclic voltammetry tests show that the electrochemical stability window of the separator is 0V to 4.5V (relative to Li / Li+), which indicates that the separator has good electrochemical stability within the voltage range commonly used in lithium batteries.
[0070] - At a charge and discharge rate of 0.5C, the battery maintained 90% of its initial capacity after 500 cycles. The Coulombic efficiency remained above 99% in each cycle, indicating that the battery has excellent cycle stability and efficient charge transfer performance.
[0071] These test results show that the semi-solid lithium battery separator with self-healing function not only has good ionic conductivity, but also performs well in electrochemical stability window and battery cycle performance. The ionic conductivity reaches 1.0×10 - 3S / cm, ensuring effective ion transport between the electrolyte and the electrode, which is essential for achieving high-performance lithium batteries. The electrochemical stability window is 0V to 4.5V, covering the operating voltage range of most lithium batteries, ensuring the chemical stability of the separator during battery operation. In addition, the battery can still maintain 90% of its initial capacity after 500 cycles, as well as a Coulombic efficiency of more than 99%, which further demonstrates the excellent performance of the separator and the long-term stability of the battery.
[0072] 3. Self-repair efficiency test:
[0073] (1) Damage manufacturing:
[0074] -Use a fine needle or blade to create microscopic scratches with a length of about 200 microns on the surface of the diaphragm to simulate the microscopic damage that may be encountered in actual use.
[0075] (2) Self-repair trigger:
[0076] - The damaged membrane sample is placed under specific conditions (eg, an environment of 25°C and 50% relative humidity) for self-repair, and the duration is set to 24 hours.
[0077] (3) Observation and analysis:
[0078] -Optical microscope observation: Before and after self-repair, the damage on the diaphragm surface was observed and recorded using an optical microscope.
[0079] (4) Test results:
[0080] -Before self-repair:
[0081] -Optical microscopy showed a clear scratch on the surface of the diaphragm, about 200 microns in length and 10 microns in width.
[0082] -Since repair:
[0083] -Optical microscopy showed that the surface of the membrane in the scratched part had been significantly smoothed, and the scratch edge was no longer obvious, indicating that the self-healing material successfully filled the damaged area. The previously obvious scratches had been filled with the newly formed polymer material, and were tightly integrated with the interface of the surrounding membrane material, making it almost impossible to distinguish the original damaged area.
[0084] According to the test results, the semi-solid lithium battery separator exhibited excellent self-repairing ability, which can significantly repair microscopic damage within 24 hours, with a self-repair efficiency of up to 95%. This shows that the self-repairing material in the separator can effectively respond to damage and restore the integrity and function of the separator through filling and cross-linking of polymer materials. This efficient self-repairing ability is of great significance for improving the safety of lithium batteries and extending their service life.
Claims
1. A semi-solid lithium battery separator with self-repairing function, characterized in that: The diaphragm comprises a plurality of microcapsules, wherein the microcapsules are filled with a monomer material which can flow out when the diaphragm is damaged and form a solid polymer at the damaged position.
2. The semi-solid lithium battery separator according to claim 1, wherein: The shell material of the microcapsule is selected from polyurethane, polylactic acid or other polymer materials with good chemical stability and mechanical strength.
3. The semi-solid lithium battery separator according to claim 1, wherein: The monomer material is an acrylic ester monomer, and the microcapsule also contains a small amount of photoinitiator or thermal initiator to promote rapid polymerization of the monomer.
4. The semi-solid lithium battery separator according to claim 1, wherein: The base material of the diaphragm is selected from polyethylene, polypropylene, polyvinyl alcohol or a composite material thereof.
5. The semi-solid lithium battery separator according to claim 1, wherein: The diameter of the microcapsules ranges from 1 micron to 50 microns.
6. The semi-solid lithium battery separator according to claim 1, wherein: The microcapsules are evenly distributed in the diaphragm.
7. The semi-solid lithium battery separator according to claim 1, wherein: The separator further comprises a reinforcing material capable of improving the mechanical strength and electrochemical stability of the separator.
8. The semi-solid lithium battery separator according to claim 1, wherein: The reinforcing material is selected from nanoparticles, carbon nanotubes, graphene or a combination thereof.
9. A method for preparing a semi-solid lithium battery separator with self-repairing function according to any one of claims 1 to 8, comprising the following steps: preparing microcapsules containing monomer materials; and uniformly dispersing the microcapsules in a diaphragm-based material; Formation of diaphragm; and post-treating the formed separator to improve its mechanical strength and electrochemical stability.
10. The method according to claim 9, wherein: The preparation of the microcapsules includes emulsion polymerization, phase transfer or microfluidics technology.
Citation Information
Cited By
Preparation method of all-solid-state lithium ion battery without diaphragm and electrolyte
CN120914354A
Dielectric elastomer-based composite diaphragm, preparation method thereof and flexible battery
CN120999244A
Diaphragm and battery
CN121149586A